The role of pro-inflammatory S100A9 in Alzheimer’s disease amyloid-neuroinflammatory cascade - Chao Wang; Alexey Klechikov; Anna L. Gharibyan; Sebastian K.T.S. Wärmländer; Jüri Jarvet; Lina Zhao; Xueen Jia; S.K. Shankar; Anders Olofsson; Thomas Brännström; Yuguang Mu; Astrid Gräslund; et al. (2013)
Pro-inflammatory S100A9 protein is increasingly recognized as an important contributor to inflammation-related neurodegeneration. Here, we provide insights into S100A9 specific mechanisms of action in Alzheimer's disease (AD). Due to its inherent amyloidogenicity S100A9 contributes to amyloid plaque formation together with Aβ. In traumatic brain injury (TBI) S100A9 itself rapidly forms amyloid plaques, which were reactive with oligomer-specific antibodies, but not with Aβ and amyloid fibrillar antibodies. They may serve as precursor-plaques for AD, implicating TBI as an AD risk factor. S100A9 was observed in some hippocampal and cortical neurons in TBI, AD and non-demented aging. In vitro S100A9 forms neurotoxic linear and annular amyloids resembling Aβ protofilaments. S100A9 amyloid cytotoxicity and native S100A9 pro-inflammatory signaling can be mitigated by its co-aggregation with Aβ, which results in a variety of micron-scale amyloid complexes. NMR and molecular docking demonstrated transient interactions between native S100A9 and Aβ. Thus, abundantly present in AD brain pro-inflammatory S100A9, possessing also intrinsic amyloidogenic properties and ability to modulate Aβ aggregation, can serve as a link between the AD amyloid and neuroinflammatory cascades and as a prospective therapeutic target.